(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the importance of using the experience of developed countries in e-commerce in Uzbekistan, the importance of developing e-commerce and the problems and solutions for the gradual development of e-commerce.